2019
DOI: 10.20944/preprints201910.0252.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iron Depletion Reduces Abce1 Transcripts While Inducing the Mitophagy Factors Pink1 and Parkin

Abstract: Lifespan extension was recently achieved in Caenorhabditis elegans nematodes by mitochondrial stress and mitophagy, triggered via iron depletion. Conversely in man, deficient mitophagy due to Pink1/Parkin mutations triggers iron accumulation in patient brain and limits survival. We now aimed to identify murine fibroblast factors, which adapt their mRNA expression to acute iron manipulation, relate to mitochondrial dysfunction and may influence survival. After iron depletion, expression of the plasma membrane r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…However, TYW5 protein was likely expressed in cortical neurons during the process of synapse formation [ 67 ]. Our study found that TYW5 is expressed in a variety of cell types in the human cerebral cortex [ 68 ], with the highest expression level in neurons and astrocytes. Our results indicate that TYW5 –associated tRNA lesions in neurons and astrocytes may be one of the potential pathological changes of SCZ [ 69 – 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, TYW5 protein was likely expressed in cortical neurons during the process of synapse formation [ 67 ]. Our study found that TYW5 is expressed in a variety of cell types in the human cerebral cortex [ 68 ], with the highest expression level in neurons and astrocytes. Our results indicate that TYW5 –associated tRNA lesions in neurons and astrocytes may be one of the potential pathological changes of SCZ [ 69 – 71 ].…”
Section: Discussionmentioning
confidence: 99%